On‐Tip Photo‐Modulated Molecular Printing. Issue 44 (9th September 2015) - Xie, Zhuang; Zhou, Yu; Hedrick, James L.; Chen, Peng‐Cheng; He, Shu; Shahjamali, Mohammad M.; Wang, Shunzhi; Zheng, Zijian; Mirkin, Chad A.
Abstract The concept of using cantilever‐free scanning probe arrays as structures that can modulate nanoscale ink flow and composition with light is introduced and evaluated. By utilizing polymer pen arrays with an opaque gold layer surrounding the base of the transparent polymer pyramids, we show that inks with photopolymerizable or isomerizable constituents can be used in conjunction with light channelled through the pyramids to control ink viscosity or composition in a dynamic manner. This on‐tip photo‐modulated molecular printing provides novel chemically and mechanically controlled approaches to regulating ink transport and composition in real time and could be useful not only for rapidly adjusting feature size but also for studying processes including photoreactions and mass transport at the nanoscale, self‐assembly, and cell–material interactions.